2019
DOI: 10.1186/s12944-019-1138-9
|View full text |Cite
|
Sign up to set email alerts
|

SOAT1 methylation is associated with coronary heart disease

Abstract: BackgroundThis study was designed to investigate whether differential DNA methylationin of cholesterol absorption candidate genes can function as a biomarker for patients with coronary heart disease (CHD).MethodsDNA methylation levels of the candidate genes FLOT1, FLOT2 and SOAT1 were measured in peripheral blood leukocytes (PBLs) from 99 patients diagnosed with CHD and 89 control subjects without CHD. A total of 110 CPG sites around promoter regions of them were examined.ResultsCompared with groups without CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A study reported that the methylation level SOAT1 is lower in patients with heart disease than normal [ 16 ]. We used the online prediction software MethPrimer ( http://www.urogene.org/methprimer ) to predict the CPG islands in SOAT1 promoter region.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study reported that the methylation level SOAT1 is lower in patients with heart disease than normal [ 16 ]. We used the online prediction software MethPrimer ( http://www.urogene.org/methprimer ) to predict the CPG islands in SOAT1 promoter region.…”
Section: Resultsmentioning
confidence: 99%
“…A study showed that the methylation level of SOAT1 in patients with coronary heart disease is significantly decreased [ 16 ]. We found that the overexpression of piRNA-6426 could increase the methylation level of SOAT1 promoter and reduce the expression levels of SOAT1 mRNA and protein, while the interference of piRNA-6426 had the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA methylation and hydroxymethylation among the elderly CHD patients were significantly upgraded. Report supported that a lower methylation level in the SOAT1 gene might enhance the risk of CHD ( Abuzhalihan et al, 2019 ).…”
Section: Dna Methylation In Vascular Aging-related Cvdmentioning
confidence: 97%